2023
DOI: 10.3390/ijerph20054661
|View full text |Cite
|
Sign up to set email alerts
|

Playground Design: Contribution to Duration of Stay and Implications for Physical Activity

Abstract: Background: The study goal was to identify playground features associated with visitor length of stay and physical activity. Methods: We observed playground visitors over 4 days during summer 2021 in 60 playgrounds in 10 US cities, selected based on design, population density, and poverty levels. We observed 4278 visitors and documented their length of stay. We observed an additional 3713 visitors for 8 min, recording their playground location, activity level, and use of electronic media. Results: People staye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Similarly, fixed-play facilities such as kiddie rides and Chinese chess tables primarily supported sanitary play behaviors. Reflecting on previous research conducted in the US [23,24] and Northern Europe [13,15] this result indicated that the carpet playground, resembling a pavement, and most of the fixed play facilities were associated with low levels of physical activity. Furthermore, the results demonstrated that the slope connecting the two parts of the park sustained a wider variety of strenuous physical activities.…”
Section: Discussionmentioning
confidence: 60%
“…Similarly, fixed-play facilities such as kiddie rides and Chinese chess tables primarily supported sanitary play behaviors. Reflecting on previous research conducted in the US [23,24] and Northern Europe [13,15] this result indicated that the carpet playground, resembling a pavement, and most of the fixed play facilities were associated with low levels of physical activity. Furthermore, the results demonstrated that the slope connecting the two parts of the park sustained a wider variety of strenuous physical activities.…”
Section: Discussionmentioning
confidence: 60%
“…(3) residential status, that is, whether a local resident or a migrant; (4) length of stay; and (5) poverty status [23].…”
Section: Social Vulnerabilitymentioning
confidence: 99%
“…(2) moderate vulnerability if it was between 0.5 and 1.0 ha; and (3) high vulnerability if it was 0.5 ha or less [23,24].…”
Section: Economic Vulnerabilitymentioning
confidence: 99%